IoT Based Healthcare System (International Journal of Innovative Research in Computer Science & Technology, 2021)
Health is a fundamental need. It is also a  human right to have access to high-quality health care.  Due to a lack of resources, India is now dealing with a  slew of health problems. This review article discusses the  concept of utilizing cutting-edge technology, such as the  Internet of Things, to solve health problems. It provides  an architectural assessment of a smart health care system  based on the Internet of Things that aims to serve  everyone with high-quality health care. Patients' bodily  parameters may be measured in real time using this  system design. Sensors gather patient body characteristics  and send them to an Arduino Uno, which then sends the  data to the cloud via a WiFI module.This information is  saved in a MySql database server, which handles  information and makes it accessible. The Android App  may be used to see this information. Which may be  installed on a smartphone, tablet, or computer? Authentication, privacy, security, and data management  are all handled via cloud computing. If the data is  abnormal, the patient and caretakers will be notified  through email. Different decision-making algorithms may  be used to make choices, and individuals can access the  database based on them. The patient has access to their  medical records. As a result, this system offers everyone  with high-quality health care as well as error-free and  seamless contact with patients.
Keywords: Internet of Thing; cloud server; Patient; Monitoring; Smart Health